Estratégias digitais para o cinema de animação independente - Daniel Leal Werneck (2005)
This paper is the result of two years of research that explored the most up-to-date possibilities of animation cinema inside the realms of digital technology and the use of personal computers in the production of animation movies. The information contained here is presented as a practical manual, full of technical and analytical inquiries. The idea is to create a text that works both for general people who are interested in the subject, and also for academical researchers. The final text will be freely distributed in the Internet, in the form of a free public website.